On harmonic summability of order a - Kandemir, Hacer Sengul; Et, Mikail (World Scientific Publ Co Pte Ltd, 2023)
In this study, the concepts of lacunary (H, 1)-summability of order a, lacunary strongly harmonic summability of order a, lacunary statistical logarithmic convergence of order a of sequences of real numbers are introduced and relations between these concepts are investigated.
Keywords: Statistical convergence; harmonic convergence; lacunary sequence